Cardiac toxicity and intervention strategies during thoracic cancer radiotherapy - Youjin Kong; Chao Yang; Lingling Xie; Yan Zhao; Zheng Rong; Xinbin Zhou; Xinbin Zhou; Wei Mao; Wei Mao (Frontiers in Oncology, 2025)
Radiation-induced heart disease (RIHD) represents a major dose-limiting complication of thoracic radiotherapy, with a multifaceted pathogenesis involving endothelial dysfunction, chronic oxidative stress, and progressive fibrotic remodeling. Emerging evidence reveals distinct molecular mechanisms underlying RIHD’s heterogeneous clinical manifestations, including pericarditis, accelerated coronary artery disease, cardiomyopathy, valvular degeneration, and conduction abnormalities—which often manifest after prolonged latency periods. Modern radiotherapy techniques have reduced but not eliminated cardiac toxicity, particularly in high-risk populations. Advanced imaging modalities and biomarkers now enable earlier detection, though diagnostic challenges persist. While current management remains largely extrapolated from conventional cardiovascular therapies, novel targeted interventions show preclinical promise. This review synthesizes contemporary understanding of RIHD pathophysiology, risk stratification paradigms, and evolving cardioprotective strategies, while highlighting critical knowledge gaps requiring translational investigation to optimize outcomes for cancer survivors.